2018
DOI: 10.1590/0103-8478cr20180345
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between single port videolaparoscopy and miniceliotomy with snock hook ovariohysterectomy techniques in bitches

Abstract: In order to use and study minimally invasive techniques to reduce side effects of ovarian-hysterectomy (OHE) in bitches, the aim of this study was to compare time, surgical complications, pain and postoperative inflammatory response, caused by single port videolaparoscopic OHE and traditional miniceliotomy with snook hook. Twenty-four healthy bitches were randomly divided in two groups: videolaparoscopy (Video) and miniceliotomy (MiniLap). Surgical time and complications, pain, need for analgesic rescue, C-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The technique uses an 11- or 12-mm trocar inserted through a skin incision performed at a site 1–2 cm below the umbilicus for the telescope insertion. This technique has been described for OVE [ 3 , 9 , 10 , 11 , 34 ], OVH [ 23 , 35 ] and for GPX in combination with OVE [ 28 ]. In all studies, the ovary suspension was performed by an external suspension suture.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The technique uses an 11- or 12-mm trocar inserted through a skin incision performed at a site 1–2 cm below the umbilicus for the telescope insertion. This technique has been described for OVE [ 3 , 9 , 10 , 11 , 34 ], OVH [ 23 , 35 ] and for GPX in combination with OVE [ 28 ]. In all studies, the ovary suspension was performed by an external suspension suture.…”
Section: Resultsmentioning
confidence: 99%
“…Binder et al [ 34 ] reported the post-operative complication rate, pain score, and owners’ satisfaction rates of SILS OVE in dogs using an OT. The results of this study were that SILS OVE with OT had minor complication rates compared to other laparoscopic techniques and had the advantages of a low post-operative pain level evaluated by the owner.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations